Static tests the stiffness of car tires. Issue 1 (February 2020) - Dudziak, M; Lewandowski, A; Waluś, K J
Abstract: Safe driving requires from the driver a number of manual actions related to the existing traffic situation. The vehicle, reacting to the imposed extortions, is subjected to three-axle loads, which are transferred by friction-shaped coupling of the tire with the surface. The generated forces affect the tread and the side of the tire, the suspension of the vehicle and the steering. The article presents the results of bench tests of two types of tires: tires with special tread (coloured) made to order and popular tires available in retail sales. The tests were carried out under static conditions. The tests were carried out in cooperation with the Stomil Tire Research and Development Center in Poznan on the position enabling acquisition and archiving of the values of forces in the function of displacement (deformation of the tire). The obtained results made it possible to determine the directional stiffness of the radial, peripheral, lateral and torsional tires. It allowed to build the stiffness characteristics and compare the response to the forced testing tires. The results obtained form the basis for analysing the scope of vehicle traffic safety, and can also be used as input data in simulation tests.